2010
DOI: 10.1186/1477-7517-7-17
|View full text |Cite
|
Sign up to set email alerts
|

Drug use and opioid substitution treatment for prisoners

Abstract: Drug use is prevalent throughout prison populations, and, despite advances in drug treatment programmes for inmates, access to and the quality of these programmes remain substantially poorer than those available for non-incarcerated drug users. Because prisoners may be at greater risk for some of the harms associated with drug use, they deserve therapeutic modalities and attitudes that are at least equal to those available for drug users outside prison. This article discusses drug use by inmates and its associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
61
0
5

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(76 citation statements)
references
References 33 publications
5
61
0
5
Order By: Relevance
“…Supporting the proposition that methadone maintenance in prisons reduces drug-related violence (Stö ver and Michels, 2010), several participants such as Hugo (37, on remand) felt that less demand for drugs meant "less chance of people getting into debt and less bullying on the [prison] wings" than had occurred when more rapid detoxification was offered. Chas reported that he though methadone maintenance was a good idea saying: I honestly do think it's a good idea because it stops me from getting in debt with someone or whatever, it's stopping me hurting [other people].…”
Section: Drug-related Violencementioning
confidence: 92%
See 1 more Smart Citation
“…Supporting the proposition that methadone maintenance in prisons reduces drug-related violence (Stö ver and Michels, 2010), several participants such as Hugo (37, on remand) felt that less demand for drugs meant "less chance of people getting into debt and less bullying on the [prison] wings" than had occurred when more rapid detoxification was offered. Chas reported that he though methadone maintenance was a good idea saying: I honestly do think it's a good idea because it stops me from getting in debt with someone or whatever, it's stopping me hurting [other people].…”
Section: Drug-related Violencementioning
confidence: 92%
“…It was also anticipated that it would enable continuation of existing treatment for people who were prescribed methadone in the community prior to prison (Stallwitz and Stö ver, 2007). A variety of additional practical and evidence-based considerations are also given for the wider introduction of methadone into adult prisons including: engaging hard-to-reach heroin using prisoners with treatment (Warren et al, 2006); stabilising heroin-dependent prisoners on entry to prison (Hughes, 2000;Stallwitz and Stö ver, 2007); reducing drug use and risky injecting behaviour in prisons, thus reducing the potential for blood-borne virus transmission (Dolan et al, 2003;Stallwitz and Stö ver, 2007;Kimber et al, 2010;Stö ver and Michels, 2010); reducing the vulnerability of drug-using prisoners to self-harm and suicide whilst in prison (Marteau et al, 2010), and to accidental opiate overdose on release (Ford et al, 2005;Department of Health (England) and The Devolved Administrations, 2007); reducing drug-related violence in prisons (Stö ver and Michels, 2010); and reducing post-release recidivism (Warren et al, 2006;Stallwitz and Stö ver, 2007;Stevens et al, 2010).…”
Section: Introductionmentioning
confidence: 98%
“…Nach Knecht & Claßen [ 49 ,vgl. 11 ,50 ,51 ] steigen die Erfolgsaussichten für Heroinabhängige im Maßregelvollzug mit der Einführung der medikamentösen Therapie (mit Methadon oder Buprenorphin) 4 . Stellt man diese Personengruppe vor die Wahl zwischen der medikamentösen Therapie und der Abstinenz, entscheidet sie sich oft für das erstere.…”
Section: Evaluationen Von Zwangsbehandlungenunclassified
“…Inside prisons in many European countries, drug use is common (Singleton et al, 2003, EMCDDA 2012. Furthermore, people who inject drugs commonly have a history of imprisonment (Stöver and Michels, 2010). Over the past two decades, the proportion of offenders sentenced for drug offences has increased markedly in the Nordic countries .…”
Section: Introductionmentioning
confidence: 99%